2014
DOI: 10.3390/land3030598
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Agricultural Landscape Change with Multiple Dimensions

Abstract: Better recognition of public perceptions is called for in developing policies that affect landscape qualities, such as agri-environmental policies. The present study focused on the evaluation of typical agricultural landscapes in Finland. We utilized and operationalized the visual landscape quality scales introduced by Tveit et al. (2006) and further explored how these scales can be applied in citizen evaluation of agricultural landscapes. From landscape data collected via an Internet survey, we analysed wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The discussion is conducted by describing the features or elements contained in the agricultural landscape including (1) Agricultural features formed by the type of agricultural land use and (2) Cultural features result from interactions between human activities and the environment, including agricultural-related structures (e.g., barns, hedging), road lanes and transmission lines and signs (boards or fences) [7,21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discussion is conducted by describing the features or elements contained in the agricultural landscape including (1) Agricultural features formed by the type of agricultural land use and (2) Cultural features result from interactions between human activities and the environment, including agricultural-related structures (e.g., barns, hedging), road lanes and transmission lines and signs (boards or fences) [7,21].…”
Section: Resultsmentioning
confidence: 99%
“…Cultural features are the results of human cultural artifacts, one of which is in the form of houses [7,21]. Through indepth interviews and observations, it was found that the farmhouses in Ngadas Village were not originally housing with a permanent material, people used to call them sudung.…”
Section: Cultural Featuresmentioning
confidence: 99%
“…Despite the obvious importance of agroecological ecosystem services, their total value is not currently included in the prices of food and agricultural products. There are few studies in Finland focusing on the non-market value of the agroecological ecosystem services (Grammatikopoulou et al 2013;Pouta et al 2014;Tienhaara et al 2020) and none of them is specifically targeted to the benefits of cropping diversification although it is a key provider of ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers from different fields have studied perceptions of residents and tourists on a variety of landscape related themes such as sense of place (Davenport & Anderson, 2005), visual aesthetics (Kalivoda et al, 2014), cultural ecosystem services (Tekken et al, 2017;Zoderer et al, 2016), rural landscape (Carneiro et al, 2015), and agricultural landscape (Grammatikopoulou et al, 2012;Pouta, Grammatikopoulou, Hurme, Soini, & Uusitalo, 2014). Studies have also demonstrated the relevance of built landscape and local culture in the overall experience of landscapes for tourists (Carneiro et al, 2015;Krausler & Pröbstl-haider, 2016;Van Zanten, Verburg, Koetse, & Van Beukering, 2014).…”
Section: Different Landscape Perceptions: Residents and Touristsmentioning
confidence: 99%